The biting midge Forcipomyia paludis (Macfie, 1936) (Diptera: Ceratopogonidae) in Slovenia, Bosnia and Herzegovina, Croatia and Sweden - Damjan Vinko; Dejan Kulijer; Magnus Billqvist; Andreas Martens (Natura Sloveniae)
Records of the biting midge Forcipomyia paludis (Macfie, 1936) from Slovenia and Bosnia and Herzegovina are reported herewith as the first finds of F. paludis in both countries, together with new records from Croatia and Sweden. This biting midge is a temporary ectoparasite of dragonfly imagines and the only ceratopogonid species known in Europe to feed specifically on this insect group. Forcipomyia paludis is already known in 18 European countries. Prior to this report, F. paludis was known to infest 67 dragonfly species in Europe. Thirteen dragonfly imagines from 11 sites in Slovenia, 27 imagines from 13 sites in Bosnia and Herzegovina and six imagines from two sites in Croatia having F. paludis on their wings were recorded. Additional data for 50 imagines from 15 sites in Sweden are also presented. In Slovenia, the species is known to occur in the Gorenjska, Goriška Brda, Vipava River Valley, Coastal-Karst region, Central Slovenia, Kočevska region and Bela krajina, while in Bosnia and Herzegovina it is known only from south Herzegovina (Ljubuški, Čapljina, Mostar and Stolac areas). In Croatia, the species is present in several parts of the country, while in Sweden it occurs only in the southern and middle parts of the country (Skåne, Öland, Gotland, Göteborg and Gävle). Six new dragonfly host species and the northernmost occurrence of F. paludis are also reported.